Antifungal Potentials of Derris indica (LAM.) Bennet Extractives - Mondal, Omar Ali; Mondal, KAMSH; Islam, Nurul (Journal of Life and Earth Science, 2014)
Antifungal activity of the D. indica (Lam.) Bennet. extractives collected in CHCl3 and methanol were tested against seven pathogenic fungi F. vasinfectum, A. fumigatus, A. niger, A. flavus, Mucor sp., C. albicans and P. notatum at concentrations of 50 and 200 ?g/disc along with a standard Nystatin (50 ?g/disc). The fruit shell extract showed activity index against C. albicans and P. notatum. The leaf and the root bark extracts were responsive on A. fumigatus, C. albicans, P. notatum and F. vasinfectum. For the root wood extract F. vasinfectum, A. fumigatus, C. albicans were responsive. For the seed, stem bark and stem wood extract showed activity index against A. flavus, C. albicans, A. fumigatus P. notatum and Mucor sp. According to the intensity of activity indices D. indica extracts (CHCl3) could be arranged in a descending order of fruit shell > leaf > root bark > root wood > seed >stem wood> stem bark extract. For the MeOH extracts the fruit shell, leaf, root bark and root wood extracts showed activity indices against A. fumigatus, C. albicans , P. notatum , Mucor sp., F vasinfectum, and A. flavus. In case of the seed, stem bark and stem wood extracts A. flavus, C. albicans, A. fumigatus, P. notatum and Mucor sp. were responsive. According to the intensity of activity indices D. indica extracts (MeOH) could be arranged in a descending order of fruit shell > leaf > root bark > root wood >seed> stem bark > stem wood extract. DOI: http://dx.doi.org/10.3329/jles.v7i0.20122 J. Life Earth Sci., Vol. 7: 61-65, 2012